Pengaruh Kualitas Pelayanan Dan Penanganan Komplain Terhadap Kepercayaan Pelanggan Kartu Pasca Bayar Pada Grapari Telkomsel Banda Aceh - Siraj, Faisal Aqil; Erlinda, Erlinda; Firdaus, Said (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Customer trust determines the survival of cellular service providers amid intense competition. Postpaid customer data at Grapari Telkomsel Banda Aceh show a declining trend since 2022, while a preliminary survey indicates a low level of customer trust. This study measures the effect of service quality and complaint handling on postpaid customer trust at Grapari Telkomsel Banda Aceh, both partially and simultaneously. The study applies a quantitative approach with a causal design. The sample consists of 100 customers, determined with the Slovin formula and drawn through convenience sampling. Primary data were collected through a Likert-scale questionnaire and analyzed with multiple linear regression. The results show that service quality significantly affects customer trust, with a calculated t value of 6.032 exceeding the table t value of 1.985 at a significance of 0.000. Complaint handling also significantly affects customer trust, with a calculated t value of 5.413 exceeding the table t value of 1.985 at a significance of 0.000. Simultaneously, both variables significantly affect customer trust, with a calculated F value of 55.921 exceeding the table F value of 3.09. The adjusted R square value of 0.526 indicates that service quality and complaint handling explain 52.6 percent of the variance in customer trust, while other variables outside the model explain the rest. Grapari Telkomsel Banda Aceh should improve its digital service system and speed up complaint resolution to strengthen customer trust further.